The Segmental Morphometric Properties of the Horse Cervical Spinal Cord: A Study of Cadaver - Sadullah Bahar; Durmus Bolat; Muhammet Lutfi Selcuk (The Scientific World Journal)
Although the cervical spinal cord (CSC) of the horse has particular importance in diseases of CNS, there is very little information about its segmental morphometry. The objective of the present study was to determine the morphometric features of the CSC segments in the horse and possible relationships among the morphometric features. The segmented CSC from five mature animals was used. Length, weight, diameter, and volume measurements of the segments were performed macroscopically. Lengths and diameters of segments were measured histologically, and area and volume measurements were performed using stereological methods. The length, weight, and volume of the CSC were 61.6±3.2 cm, 107.2±10.4 g, and 95.5±8.3 cm3, respectively. The length of the segments was increased from C1 to C3, while it decreased from C3 to C8. The gross section (GS), white matter (WM), grey matter (GM), dorsal horn (DH), and ventral horn (VH) had the largest cross-section areas at C8. The highest volume was found for the total segment and WM at C4, GM, DH, and VH at C7, and the central canal (CC) at C3. The data obtained not only contribute to the knowledge of the normal anatomy of the CSC but may also provide reference data for veterinary pathologists and clinicians.